The new perspective of cardiac exercise rehabilitation: based on integrative physiology - You, Guopeng; Xie, Jinwen; Tong, Wei; Zhao, Shaocong (Frontiers in Physiology, 2025)
Cardiovascular diseases (CVDs) are the world’s leading cause of death, but there’s a gap between scientific research and real-world treatment. Exercise is a safe and effective way to prevent and manage CVDs, yet putting it into practice faces many challenges. This review shows how exercise protects the heart by improving metabolism, reducing inflammation and cell damage, and strengthening connections between heart cells and blood vessels. Exercise establishes a multi-organ defense network involving remote organs including the brain, skeletal muscle, adipose tissue, liver, and kidneys. To bridge the gap between research and clinical use, future efforts should focus on developing exercise-like drugs, personalized workout plans, and remote rehabilitation programs.